Wideband microstrip antenna integrated with optimized buffer layer parameters for underwater wireless communication / Hanisah Mohd Zali ... [et al.] - Mohd Zali, Hanisah; Ibrahim, Idnin Pasya; Ali, Mohd Tarmizi; Mahmood, Mohd Khairil Azhar (Universiti Teknologi MARA, 2019)
Transmitting electromagnetic waves in underwater environment is a challenge, due to the lossy properties of water. Using conventional antennas for transmission in these environments results in severe signal attenuation, partly attributed to un-optimized antenna parameters. In this paper, a conventional wideband circular patch antenna integrated with an optimized buffer layer structure was proposed for underwater applications. From simulation, the optimized buffer materials and sizes shows improvements in antenna performance while operating underwater within a wide frequency range. The antenna with the optimized buffer layer was fabricated and measured in a laboratory water tank for verification. The measurement results agree well with the simulated results, verifying the effectiveness of the utilization of an optimized buffer layer in underwater environment.